2016
DOI: 10.1002/ange.201604290
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable NIR‐Emitting Gold Nanoparticles

Abstract: Photo-switching of the NIR emission of gold nanoparticles (GNP) upon photo-isomerization of azobenzenel igands,b ound to the surface,i sd emonstrated. Photophysical results confirm the occurrence of an excitation energy transfer process from the ligands to the GNP that produces sensitized NIR emission. Because of this process,the excitation efficiency of the gold core,u pon excitation of the ligands,i s muchh igher for the trans form than for the cis one,a nd t!c photo-isomerization causes ar elevant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…More recently, we proposed a different strategy to turn on/off the PL of Au 144 NCs using as organic sensitizer a photo‐switchable azobenzene derivative (Figure ) . The conversion of the trans form of the ligand into the cis one took place almost quantitatively (> 95 %) with a quantum yield identical to the one measured for the same molecule free in solution (upon irradiation at 360 nm).…”
Section: Improving Brightness Of Gncsmentioning
confidence: 96%
See 2 more Smart Citations
“…More recently, we proposed a different strategy to turn on/off the PL of Au 144 NCs using as organic sensitizer a photo‐switchable azobenzene derivative (Figure ) . The conversion of the trans form of the ligand into the cis one took place almost quantitatively (> 95 %) with a quantum yield identical to the one measured for the same molecule free in solution (upon irradiation at 360 nm).…”
Section: Improving Brightness Of Gncsmentioning
confidence: 96%
“…In order to improve this feature, our and other groups proposed the design of hybrid structures that combine the PL properties of Au NCs with the optical properties of organic dyes in order to enhance the brightness of the inorganic emitters. A considerable improvement of brightness can in fact be achieved by introducing ligands able to efficiently adsorb light (chromophores) and to transfer the excitation energy to the emitting gold core , …”
Section: Improving Brightness Of Gncsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dimensional plasmonic nanoparticle assemblies with new optical properties have recently attracted considerable attention because of the near-field coupling between adjacent particles (Liu D. et al, 2018 ; Li and Yin, 2019 ; Li et al, 2020a ). The ideal way is the reversible assembly of such plasmonic nanostructures, which could enable dynamic tuning of the surface plasmon coupling by responding the external stimuli, and therefore by taking advantage of the ultrasensitive gap-dependent properties of plasmonic coupling, they have great promises for applications such as colorimetric sensors, bio- and chemical detection, and therapeutics (Bonacchi et al, 2016 ; Pillai et al, 2016 ; Liu L. et al, 2018 ; Zhou et al, 2021 ). Recent studies have demonstrated the reversible assembly by controlling the nanoparticle separation via various methods, for example, by modulating solvent composition to change the ionic strength of the solution, adding moisture, thermo-, photo-, magnetical-, and pH-responsive ligands, or reversible linking molecules (such as DNA) (Liu et al, 2012 ; Liu L. et al, 2019 ; Ding et al, 2016 ; Fan et al, 2016 ; He et al, 2016 , 2019 ; Grzelczak et al, 2019 ; Li et al, 2020b ; Severoni et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, PGNPs covered with the most diverse functional groups have been synthesized and studied. 2 For example, crown ethers, 3 mono-and polysaccharides, 4 nucleic acids, 5,6 peptides, 7,8 chromophores, 9 catalysts, 10,11 and charged headgroups have been used 12−15 (Figure 1). One of the reasons that prompted the realization of such a diverse variety of structures is the observation that the coating layer has a micelle-like structure (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%